0112 Work environment and health in denmark – risk factors related to physical work demands for long-term sickness absence. (21st August 2017) - Andersen, Lars L
Abstract : In 2012, more than 20 000 people of the general working population in Demark replied to the questionnaire Work Environment and Health. The aim of the present study is to prospectively analyse risk factors for long-term sickness absence related to physical work demands. The questionnaire from 2012 will be merged with a register of social transfer payment (DREAM) and followed up for two years after the questionnaire reply. Using cox-regression analyses, the risk of register-based sickness absence of at least 6 consecutive weeks from factors related to physical work demands will be determined. Analyses will be controlled for age, gender, lifestyle, psychosocial work factors, and socioeconomic status. The questionnaire and register has just been merged, and the analyses will be performed during April-June of 2017. The first results of this study will be presented at the conference as hazard ratios and 95% confidence intervals. Based on the results, the potential for preventing long-term sickness absence at workplaces will be discussed.